Cardiovascular effects of intensive lifestyle intervention in adults with overweight/obesity and type 2 diabetes according to body weight time in range. (July 2022) - Liu, Menghui; Huang, Rihua; Xu, Lin; Zhang, Shaozhao; Zhong, Xiangbin; Chen, Xiaohong; Lin, Yifen; Xiong, Zhenyu; Wang, Lichun; Liao, Xinxue; Zhuang, Xiaodong
Summary: Background: We aimed to assess whether the cardiovascular effects of intensive lifestyle intervention (ILI) vary for those who can maintain the lower body weight after weight loss through ILI. Methods: In the secondary analysis of the Look AHEAD trial, we identified the status of weight loss for the participants in the ILI arm based on body weight time in range (TIR). These participants were allocated to three groups according to body weight TIR: 0% ( n  = 727), >0% to 50% ( n  = 656), and >50% to 100% ( n  = 811). For each group, cardiovascular outcomes were compared with matched participants receiving diabetes support & education (DSE) using 1:1 propensity score matching and Cox regression. Findings: During a median of 9·5 years of follow-up, participants with TIR of >50% to 100% can effectively maintain their body weight after weight loss through ILI; participants with TIR of 0% or >0% to 50% do not achieve or maintain weight loss. Compared with the corresponding matched participants in the DSE arm, participants with TIR of >50% to 100% in the ILI arm had a 45% lower risk of the primary outcome (HR 0·55, 95% CI 0·40–0·76), and no significant effects were found on the risk of the primary outcome in participants with TIR of 0% (HR 1·12, 95% CI 0·86–1·46) or >0% to 50% (HR 1·14, 95% CI 0·85–1·52). Interpretation: In adults with overweight/obesity and type 2 diabetes, ILI might help in lowering the risk of cardiovascular events when the lower body weight is maintained after weight loss. Funding: None.